SPATIOTEMPORAL VARIABILITY OF DROUGHT IN ROMANIA DURING 1901-2021 USING THE STANDARDIZED PRECIPITATION EVAPOTRANSPIRATION INDEX (SPEI) - Carmen Andreea BĂDĂLUȚĂ; Aritina HALIUC; Gheorghe BĂDĂLUȚĂ; Ramona Elena SCRIBAN (Analele Universităţii din Oradea: Seria Geografie)
Drought represents one of the most frequent climatic events with impact on the environment, economy and society. In this study, we analyse the drought characteristics in Romania during the period 1901-2021, using a meteorological drought index: the Standardized Precipitation Evapotranspiration Index (SPEI). To provide a clear image over time, we have divided the data into four time periods: 1901 – 1930, 1931 – 1960, 1960 – 1990, and 1991-2021. The results indicate that the period between 1901 to 1930 is characterized by moderate droughts, in contrast to the period between 1991-2021 when extreme droughts prevailed. Also, the SPEI3's spatial analysis indicates that Romania's eastern and southeastern parts are becoming drier. This study provides a clear image of climate change and indicates that the extreme drought events affected Romania in the previous decade.